The UF/IFAS Strawberry Clean Plant Program - Catalina Moyer; Natalia Peres; Vance M Whitaker (EDIS)
Florida strawberry growers primarily utilize cultivars developed by the UF/IFAS Strawberry Breeding Program. These cultivars are bred to provide the yield and quality traits needed by the Florida industry. Yet if a new cultivar has the traits that Florida growers need but pathogen-tested planting stock is not available to growers, the cultivar’s impact will be limited. The Clean Plant Program generates the pathogen-tested planting stock that nurseries and growers require. This new 5-page publication of the UF/IFAS Horticultural Sciences Department, written by Catalina Moyer, Natalia A. Peres, and Vance M. Whitaker, is intended to educate both the industry and the public on the importance of the Clean Plant Program and the methods used to produce planting stock of new cultivars. https://edis.ifas.ufl.edu/hs1343